2012
DOI: 10.1128/aac.00753-12
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Activity of Intramuscular Peramivir in Mice Infected with a Recombinant Influenza A/WSN/33 (H1N1) Virus Containing the H275Y Neuraminidase Mutation

Abstract: The therapeutic activity of intramuscular (IM) peramivir was evaluated in mice infected with a recombinant influenza A/WSN/33 virus containing the H275Y neuraminidase (NA) mutation known to confer oseltamivir resistance. Regimens consisted of single (90 mg/kg of body weight) or multiple (45 mg/kg daily for 5 days) IM peramivir doses that were initiated 24 h or 48 h postinfection (p.i.). An oral oseltamivir regimen (1 or 10 mg/kg daily for 5 days) was used for comparison. Untreated animals had a mortality rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…For patients on mechanical ventilation, if intravenous zanamivir is not available, other therapeutic options include inhaled or systemic ribavirin or parenteral peramivir, a NAI that is currently approved in Japan and South Korea. Although the H275Y mutant exhibits highly reduced inhibition to peramivir in vitro , animal studies using the A/WSN/33 (H1N1) virus indicated that a single administration (90 mg/kg intramuscularly) or multiple daily doses (45 mg/kg × 5 days) of this compound successfully prevented mortality and significantly decreased weight loss and lung viral titers after infection with the H275Y mutant . Such clinical benefits are likely attributable to the high concentrations of peramivir (4000‐ to 8000‐fold higher than the IC 50 value in plasma), its high binding affinity and slow off‐rate from the NA .…”
Section: Management Of Oseltamivir‐resistant Severe Influenza a Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients on mechanical ventilation, if intravenous zanamivir is not available, other therapeutic options include inhaled or systemic ribavirin or parenteral peramivir, a NAI that is currently approved in Japan and South Korea. Although the H275Y mutant exhibits highly reduced inhibition to peramivir in vitro , animal studies using the A/WSN/33 (H1N1) virus indicated that a single administration (90 mg/kg intramuscularly) or multiple daily doses (45 mg/kg × 5 days) of this compound successfully prevented mortality and significantly decreased weight loss and lung viral titers after infection with the H275Y mutant . Such clinical benefits are likely attributable to the high concentrations of peramivir (4000‐ to 8000‐fold higher than the IC 50 value in plasma), its high binding affinity and slow off‐rate from the NA .…”
Section: Management Of Oseltamivir‐resistant Severe Influenza a Infecmentioning
confidence: 99%
“…42 Such clinical benefits are likely attributable to the high concentrations of peramivir (4000-to 8000-fold higher than the IC 50 value in plasma), its high binding affinity and slow off-rate from the NA. 42,43 However, because of the emergence of the H275Y mutation in a few patients receiving peramivir during the 2009 pandemic (through an emergency access program), 44 other studies are needed before recommending such therapeutic modality in that context. An algorithm for the management of oseltamivirresistant infections is proposed in the Figure 1.…”
Section: Management Of Oseltamivir-resistant Severe Influenza a Infecmentioning
confidence: 99%
“…Pengobatan infeksi influenza dengan antiviral peramivir yang diberikan melalui intravena atau intramuskular dapat menjadi alternatif pemberian bagi pasien yang tidak dapat diberi pengobatan zanamivir (inhalasi) dan oseltamivir (oral). Pemberian peramivir dengan dosis tunggal maupun ganda bersifat efektif untuk pengobatan infeksi virus avian influenza H1N1 yang resisten terhadap oseltamivir yang mengalami mutasi H275Y pada protein NA (Abed et al 2012).…”
Section: Antiviralunclassified
“…117 Intramuscular peramivir would still be effective in mice infected with influenza A/WSN/33 (H1N1) virus containing the H274Y neuraminidase mutation. 118 Yet, in vitro passaging of influenza A (H1N1) selected for a virus, containing both D198G and H274Y mutations, that was highly resistant to oseltamivir and peramivir, but not zanamivir. 119 This raises the question as to whether the neuraminidase oseltamivir-resistance mutation H274Y engenders cross-resistance to peramivir in vivo, in humans.…”
Section: H Antiviral Agents Active Against Influenza a Viruses: Peramentioning
confidence: 99%
“…Resistance to oseltamivir has arisen due to mutation H274Y in the neuraminidase of influenza A (H1N1) . Intramuscular peramivir would still be effective in mice infected with influenza A/WSN/33 (H1N1) virus containing the H274Y neuraminidase mutation . Yet, in vitro passaging of influenza A (H1N1) selected for a virus, containing both D198G and H274Y mutations, that was highly resistant to oseltamivir and peramivir, but not zanamivir .…”
Section: Introductionmentioning
confidence: 99%